Implementation of Pierce Similarity Distance Algorithm to Detect Harfu Jar In the Quran As a Basic Learning media Of Arabic Language Science - Miftahul Jannah; Adli Abdillah Nababan (Institute of Computer Science (IOCS), 2020)
Arabic is a language that is rich in rules and rules in composing sentences and understanding speech. As we know, a collection of Arabic languages ​​is found in the Holy Qur'an of the Islamic Ummah. In the Al-Quran there are many jar letters that have special meanings in each letter. In Arabic language rules, In the Letters jar is a letter whose job is to give a hard line in the sentence in front of it. The purpose of this study is to build a basic Arabic learning media in detecting JAR letters using the pierce similarity method. In building the system, an image processing theory approach is carried out. The stages of the detection system process begin with the file.bmp extension process of the original image, then resizing, namely the process of placing the image to the specified coordinate points, Grayscale, convolution or edge detection and distance calculation with Pierce similarity where this algorithm will store the value of bits in the pattern of letters that are trained and then will match the values ​​in the image to be tested. Input image is the result of drawing the verses of the Quran.